2010
DOI: 10.1016/j.ejcts.2009.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral functions and metabolism after antegrade selective cerebral perfusion in aortic arch surgery

Abstract: There was no evidence of ischaemic brain injury after ASCP even if some degree of reversible brain oedema secondary to cardiopulmonary bypass (CPB) was present. The cognitive outcomes in patients undergoing ASCP were comparable to patients undergoing coronary artery bypass. The lack of left subclavian artery perfusion during cerebral perfusion leads to temporary glucose hypometabolism in the occipital lobes without neuronal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 24 publications
1
17
0
2
Order By: Relevance
“…Currently, it has been largely demonstrated that optimizing cerebral protection with hypothermia and adjunctive cerebral perfusion allows for safe, extended periods of circulatory arrest and open arch reconstruction (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it has been largely demonstrated that optimizing cerebral protection with hypothermia and adjunctive cerebral perfusion allows for safe, extended periods of circulatory arrest and open arch reconstruction (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Kompleks aortik prosedürlerde derin HSA ve antegrad selektif serebral perfüzyon (ASSP) uygulaması serebral koruma için sık tercih edilen bir yöntemdir (2) . Derin HSA ve ASSP sırasında selektif serebral kan akım hızı, selektif perfüzyon süresi, sistemik soğu-manın derecesi, asit-baz stratejisi, hemodilüsyon derecesi gibi birçok faktör sonuca etki edebilir (3,4) . Bütün bu uygulamaların ve medikasyonların etkisini gözlemek amacıyla serebral monitorizasyon teknikleri kullanılır.…”
Section: Introductionunclassified
“…(3) Cerebral oxygen consumption is significantly reduced during cooling but, as demonstrated by some experimental studies, at 30 8C it starts to increase after 15 min of selective cerebral perfusion and some ischaemic alterations can occur if the blood supply is not sufficient [7]. (4) A variable degree of hypoperfusion of the vertebrobasilar system without neuronal injury has been demonstrated in humans, most likely related to the lack of left subclavian artery perfusion, during long periods of bilateral ASCP [8]. (5) Reversible brain oedema occurs during bilateral ASCP [8].…”
mentioning
confidence: 97%
“…(4) A variable degree of hypoperfusion of the vertebrobasilar system without neuronal injury has been demonstrated in humans, most likely related to the lack of left subclavian artery perfusion, during long periods of bilateral ASCP [8]. (5) Reversible brain oedema occurs during bilateral ASCP [8]. The mechanism of oedema is not completely understood and a single specific aetiology cannot be identified.…”
mentioning
confidence: 98%